2016
DOI: 10.1093/femsec/fiw044
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the relative importance of host tree community, abiotic environment and spatial factors on ectomycorrhizal fungal assemblages along an elevation gradient

Abstract: Recent studies have shown that changes in community compositions of ectomycorrhizal (ECM) fungi along elevation gradients are mainly affected by changes in host tree communities and/or in abiotic environments. However, few studies have taken the effects of processes related to fungal dispersal (i.e. spatial processes) into account and distinguished the effects of host community, abiotic environment and spatial processes on community composition along elevation gradients. This has left unclear the relative impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 63 publications
6
56
1
Order By: Relevance
“…In the whole forest, total, saprotrophic, pathogenic and EM fungal community compositions were significantly related to various combinations of edaphic, geographic and plant‐related variables, as reported in previous studies (e.g. Pellissier et al ., ; Tedersoo et al ., ; Prober et al ., ; Matsuoka et al ., ). Furthermore, we found that different combinations of abiotic variables were correlated with these fungal compositions between ridge and valley habitats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the whole forest, total, saprotrophic, pathogenic and EM fungal community compositions were significantly related to various combinations of edaphic, geographic and plant‐related variables, as reported in previous studies (e.g. Pellissier et al ., ; Tedersoo et al ., ; Prober et al ., ; Matsuoka et al ., ). Furthermore, we found that different combinations of abiotic variables were correlated with these fungal compositions between ridge and valley habitats.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have found that the diversity of microbes may show various responses to increases in altitude, including no significant change, increases, reductions, or hump-shaped patterns (e.g. Fierer et al, 2011;Bahram et al, 2012;Pellissier et al, 2014;Matsuoka et al, 2016). These variations in plant and microbial altitudinal diversity patterns may arise because plant diversity is mainly determined by temperature and dispersal limitation (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, recent studies have shown that dispersal of ECM fungi is limited spatially, even at a few kilometers, and that this dispersal limitation can generate spatial structures in ECM fungal communities independent of environmental factors (Peay et al , 2012; Peay & Bruns, 2014). Thus far, the effects of these factors have been investigated at relatively small spatial scales, from forest to landscape scales (e.g., Tedersooet et al , 2011; Bahram et al , 2012; Matsuoka et al , 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Rivers typically consist of a network of multiple branches that originate from the main stream. Terrestrial fungal communities have spatial structures wherein geographically closer sites share similar fungal communities which reflects the surrounding environment and dispersal ability of each species (Talbot et al, 2014; Matsuoka et al, 2016b; Peay et al, 2016). Assuming that fungal DNA assemblages in river water reflect the fungal community compositions of surrounding land, the assemblages also indicate the spatial structure.…”
Section: Introductionmentioning
confidence: 99%